Prosodic Morphology: A Refined Analysis - Harrif, Maroua (International Journal of Linguistics and Translation Studies, 2025)
This paper offers a refined analysis of Prosodic Morphology, emphasizing the role of prosodic constraints in shaping morphological processes such as reduplication and truncation. Building on the foundational work of McCarthy and Prince, the study illustrates how prosodic units—syllables, feet, and prosodic words—govern non-linear morphological patterns. Drawing on examples from Moroccan Arabic, the paper demonstrates how the processes of truncation and reduplication are systematically constrained by prosodic structures, adhering to minimal word requirements and syllable-based templates. The findings support the broader theoretical claim that morphological operations are deeply rooted in phonological organization. Additionally, they contribute to our understanding of cross-linguistic variation in non-concatenative morphology. Integrating insights from Optimality Theory, the study also discusses the limitations and broader implications of Prosodic Morphology as a framework for analyzing complex linguistic phenomena.